The effect of pre-class quizzes assisted flipped classroom learning on student learning outcomes in the biochemistry course of fatty acid metabolism - Safitri, Erni; Sofia, Baiq Fara Dwirani; Ningsih, Baiq Nila Sari; Savalas, Lalu Rudyat Telly (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
The study aims to determine the effect of the flipped classroom learning model assisted by pre-class quizzes on student learning outcomes of the Faculty of Mathematics and Natural Sciences, University of Mataram, in the subject of biochemistry, on fatty acid metabolism. The type of experimental research used in this study was a Quasi-Experimental Design with a Post-Test Only Non-Equivalent Control Group Design. The population in this study was the sixth-semester students of the Faculty of Mathematics and Natural Sciences, Mataram University, for the 2022 academic year, totaling 60 people with a sampling technique using saturated sampling. In this research, two classes were used: the control and experimental classes. In the experimental class, namely class A, the flipped classroom learning model was treated with the help of pre-class quizzes, while the control class only used the flipped classroom model without pre-class quizzes. This study measured student learning outcomes from post-test question scores with 30 multiple-choice questions. The data analysis techniques used are normality test, homogeneity test, hypothesis test using paired sample t-test, and effect size test. Based on the results of data analysis using the normality test and homogeneity test that was carried out, the data was usually and homogeneously distributed, so hypothesis testing was carried out using the t-test and effect size test. Based on the hypothesis testing that has been carried out, there is an influence of the flipped classroom learning model assisted by pre-class quizzes on student learning outcomes in the biochemistry course on fatty acid metabolism. This can be seen from the sig value. (2-tailed) of 0.000 in the paired sample t-test, resulting in the interpretation that H0 is rejected and H1 is accepted. As for the magnitude of the effect of the flipped classroom model assisted by pre-class quizzes using the effect size calculation formula, the result was 1.33, which shows the criteria for a high effect value.